An investigation of student leadership in an independent school in the Eastern Cape: Êºdo alternative forms of leadership (such as servant leadership) emerge through community building?Êº - Knott-Craig, Ian Duncan (Rhodes University, Faculty of Education, Department of Education, 2008)
Significant changes have taken place in recent years in leadership theory and practice world wide. Theorizations of effective leadership have evolved from being authoritarian and task-centered to a model in which leaders are encouraged to look beyond their self-interest and prioritize the interests of the group. This study investigates the development of an alternative form of leadership through community building in two male school boarding houses. It attempts to ascertain whether students are able to work collaboratively towards developing an environment conducive to servant leadership. Structured according to the transformative research paradigm, this action research study was conducted in an independent school, Kingswood College, in Grahamstown, South Africa. The College is a traditional independent co-educational school that prides itself on producing leaders. As the school was in the process of reviewing its leadership system, it became an appropriate site to investigate the development of community and to explore possibilities for the emergence of an alternative form of leadership that would reflect the attributes of servant leadership. The participants in the study were volunteers from two boarding houses, who agreed to reflect on their perceptions and experiences of the way in which their houses functioned. My research findings show that through their willingness to engage in moral dialogue, students can transform their boarding houses into closely-knit communities bound together by shared values and beliefs. Closer relationships make for better understanding. As the leaders take on the responsibility of caring for their juniors, a moral obligation begins to manifest itself. Leaders will display the attributes of servant leadership if they are prepared to acknowledge in practice this moral obligation to serve others.
Keywords: Kingswood College; Private schools -- South Africa -- Eastern Cape; Servant leadership -- South Africa -- Eastern Cape; Educational leadership -- South Africa -- Eastern Cape; Community and school -- South Africa -- Eastern Cape; Student volunteers in social service -- South Africa -- Eastern Cape